The genetically predicted causal relationship of inflammatory bowel disease with bone mineral density and osteoporosis: evidence from two-sample Mendelian randomization - Xu, Dengyong; Chen, Yao; Gao, Xing; Xie, Weidong; Wang, Ya; Shen, Jiaying; Yang, Guang; Xie, Binbin (Frontiers in Immunology, 2023)
Background: Many existing studies indicated that patients with inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), tend to have the risk of low total body bone mineral density (BMD), and are more likely to have osteoporosis (OS). To determine the causal relationship between IBD and bone metabolic disorders, we herein performed a two-sample Mendelian randomization analysis (TSMR) using publicly available summary statistics. Methods: Summary statistics of total body BMD, OS and IBD were downloaded from the Open Genome-Wide Association Study (GWAS), FinnGen consortium and International Inflammatory Bowel Disease Genetics Consortium (IIBDGC). The European and East Asian populations have consisted in this Mendelian Randomization (MR) work. A range of quality control procedures were taken to select eligible instrument SNPs closely associated with total body BMD, OS and IBD. To make the conclusions more reliable, we applied five robust analytical methods, among which the inverse variance weighting (IVW) method acted as the major method. Besides, heterogeneity, pleiotropy and sensitivity were evaluated. Results: In the European population, the genetic association of UC on total body BMD (OR=0.97, 95%CI=0.96,0.99, P<0.001) and overall IBD on total body BMD (OR=0.98, 95%CI=0.97,1.00, P=0.013) were significant, while the effect of CD on total body BMD was not significant enough (OR=0.99, 95%CI=0.98,1.00, P=0.085). All of UC, CD and overall IBD can be the genetic risk factor of having OS with pathological fracture (UC: OR=1.13, 95%CI=1.02,1.26, P=0.024, CD: OR=1.14, 95%CI=1.05,1.25, P=0.003, overall IBD: OR=1.13, 95%CI=1.02,1.24, P=0.015). In East Asian groups, only CD had a causal relationship with OS (OR=1.04, 95% CI=1.01,1.07, P=0.019). Conclusion: Our study revealed genetically predicted associations between IBD on total body BMD and OS in European and East Asian populations. This work supplemented the results of previous retrospective studies and demonstrated the necessity of BMD monitoring in patients with IBD.